Robust and effective method for automatic generation of one-dimensional transfer functions - Mesquita, Rustam; Celes, Waldemar (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and Images, 2019)
In direct volume rendering, the use of transfer functions allows the visualization of specific parts of the volume, revealing significant structures such as boundaries between different materials. To interactively specify an adequate transfer function is a very challenging and time-consuming task. Besides, a user can settle with a transfer function that does not reveal the overall structure inside the volume. Hence, the importance of generating adequate transfer functions automatically. Since Kindlmann and Durkin's seminal work on the semi-automatic generation of transfer functions, many research works have been conducted attempting to improve their proposal. Despite some fine resulting visualizations, many of these works aimed to diminish the problem of boundary overlaps, in the data domain, by using two-dimensional transfer functions, thus decreasing the focus on the automatic generation and leaving to the user, again, the task to manually isolate isosurfaces. Moreover, fine-tuning two-dimensional transfer functions is less intuitive than adjusting one-dimensional ones. This paper redirects Kindlmann and Durkin's concepts of boundary characterization and proposes a new method to automatically generate one-dimensional transfer functions, more robust to boundary overlaps. This work also suggests a rendering filter to isolate detected isosurfaces in the visualization.